Thales on Water - Legutko, Ryszard (Peitho. Examina Antiqua, 2017)
The paper attempts to reconstruct Thales’ argument about water, which is rightly considered to be the core of his philosophy of nature. It consists of two separate arguments – one biological and the other physical – which ascribe to water two different functions: in the first case, it is a source of life on the earth or, in another version, a source of life of the earth in its entirety; in the second case, it is something that supports the earth in its stationary position in the cosmos. These two arguments indicate that Thales’ notion of water was meant to answer more than just one question about nature. This, in turn, might justify the use of the concept of arche, which Aristotle attributed to the Ionian philosophers, even though Thales had obviously never used the term. The concept may somehow accurately render Thales’ more general view of water. It should be noted, however, that if the term arche can be applied to Thales’ views, then it is only in the sense related to the “coming-to-be”. Thales’ arguments did not apply – contrary to what some doxographers said and what certain scholars still maintain – to the question of the end, or perishing of physical things, the problem taken up only by later Ionians. To put it differently, Thales never claimed that the physical things which die or undergo destruction change into water.